COPY RIGHT PROTECTION FOR NETFLIX STREAMING VIDEO CIRCULATED IN TELEGRAM - Ishma Safira; Efridani Lubis; Fauziah Fauziah (Jurnal Hukum Jurisdictie, 2022)
This study discusses copyright protection for Netflix streaming videos circulating on Telegram, where technological developments, especially in the field of information (internet) are widely used by irresponsible people by circulating Netflix streaming videos on Telegram which can be watched by the general public without subscribing. The author examines the forms of copyright infringement on the circulation of Netflix streaming videos on Telegram and how the copyright protection of Netflix streaming videos circulating on Telegram is based on the laws and regulations in force in Indonesia. The research method used is normative juridical with a law approach and a conceptual approach. The results of the study conclude that the form of copyright protection for Netflix streaming videos circulating on Telegram is regulated in Indonesian laws and regulations, namely UUHC Number 28 of 2014, ITE Law Number 19 of 2016, and Law Number 33 of 2009 concerning Film. Copyright protection that can be done on Netflix streaming videos circulating on Telegram is preventive and repressive protection. Thus, it can be seen that the government's efforts as a form of preventive protection are urgently needed with socialization to the public not to use pirated products and repressive efforts by becoming a forum for following up on reports of copyright infringement in order to reduce piracy in Indonesia.